Purification of FAME by rice hull ash adsorption - Ozgul-Yucel, Sevil; Turkay, S. (Wiley, 2003)
AbstractRice hull ash (RHA) and silica gel were used for purification of FAME by adsorption of FFA at atmospheric conditions. Studies demonstrated that silica gel is a better adsorbent than RHA in purifying FAME. However, both adsorbents were effective in reducing FFA levels from FAME extracts. The FFA adsorption efficiency increased with high FAME concentration and high adsorbent dosage. But FAME adsorption also increased with larger doses of adsorbent. The adsorption isotherms of FFA were determined with both adsorbents. FFA adsorption displayed Freundlich‐type isotherms.